Two experiments in the perception of Fø timing in Danish - Thorsen, Nina (Annual Report of the Institute of Phonetics University of Copenhagen, 1983)
The perceptual relevance of rather finely timed differences in the occurrence of fundamental frequency (Fø) rises as observed in natural speech is established in listening experiments with synthetic speech stimulus material. (1) When vowel and consonant duration cues are ambiguous between /ku•lə/ and /kulə/ an early Fø rise, relative to the vowel-consonant boundary, will tend to favour identification of stimuli as /ku•lə/, while a later Fø rise increases the number of /kulə/ judgments somewhat. (2) When vowel duration cues are ambiguous between /’bilisd/ and /bi’lisd/ an Fø rise before the intervocalic consonant will significantly increase the number of /’bilisd/ identifications, whereas an Fø rise after the consonant yields more judgments of /bi’ lisd/. The latter result corroborates the acoustic observation that initial voiced consonants in stressed syllables dissociate tonally from the vowel and join up with the preceding material, if any, to the effect that tonally the stress seems to begin with the vowel.